Solitary wave solutions of coupled boussinesq equation. (11th May 2016) - Abazari, Reza; Jamshidzadeh, Shabnam; Biswas, Anjan
Abstract : This article presents the general case‐study of our previous works regarding generalized Boussinesq equations [17, 18, 19], that focus on application of various subordinate methods where are applied to construct more general exact solutions of the coupled Boussinesq equations. In this article, the ( G ′ / G ) ‐expansion method is applied on coupled Boussinesq equations. Our work is motivated by the fact that the ( G ′ / G ) ‐expansion method provides not only more general forms of solutions but also periodic, solitary waves, and rational solutions. The method appears to be easier and faster by means of a symbolic manipulation program. © 2016 Wiley Periodicals, Inc. Complexity 21: 151–155, 2016